Studies towards the total synthesis of manzamine A - Hawkins, A (2013)
This thesis describes studies towards the total synthesis of manzamine A (9), a marine alkaloid. Two routes are presented. The first route applied a novel palladium-catalysed arylative allene spirocyclisation cascade to the synthesis of manzamine A (9). In the first generation, a short route was developed to access the tricyclic ACE core 263a in only nine steps. The second generation applied the palladium-catalysed cascade to a similar system which utilised non-terminal allene pro-nucleophile 450 in an attempt to access a homologated derivative of the ACE core. The second route relied on a diastereoselective Michael addition between nitro-olefin 473 and 8,5-fused ring system 146 comprising rings C and E of manzamine A (9). Further elaboration of the Michael addition product enabled the synthesis of tetracyclic ABCE core precursor 464 to be carried out and preliminary investigations into ring B formation were investigated.